Sulfide solid electrolyte, manufacturing method thereof, and all-solid-state battery

The sulfide solid electrolyte composition (100-x)[yLi2S·(1-y)P2S5]·xLiBH4, produced via mechanical milling and heat treatment, addresses the issue of low conductivity in existing electrolytes, resulting in improved battery performance.

JP2024176679AActive Publication Date: 2024-12-19TOYOTA JIDOSHA KK
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023095415
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-09
Publication Date
2024-12-19
Estimated Expiration
2043-06-09

AI Technical Summary

Technical Problem

Existing sulfide solid electrolytes in all-solid-state batteries exhibit insufficient ionic conductivity, limiting battery performance.

Method used

A sulfide solid electrolyte composition of (100-x)[yLi2S·(1-y)P2S5]·xLiBH4 is produced through a mechanical milling process with specific gravity conditions and a heat treatment step, resulting in a sulfide solid electrolyte with ionic conductivity of 5.0 mS/cm or more.

Benefits of technology

The new electrolyte composition achieves significantly improved ionic conductivity, enhancing the performance of all-solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024176679000001_ABST
    Figure 2024176679000001_ABST
Patent Text Reader

Abstract

To provide a sulfide solid electrolyte having good ion conductivity.SOLUTION: There are provided a sulfide solid electrolyte for use in an all-solid-state battery, the sulfide solid electrolyte has a composition represented by (100-x)[yLi2S (1-y)P2S5] xLiBH4 (x is a number that satisfies 50<x<75, and y is a number that satisfies 0.72≤y≤0.78), and an ionic conductivity at 25°C of 5.0 mS / cm or more.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a sulfide solid electrolyte, a method for producing a sulfide solid electrolyte, and an all-solid-state battery. [Background technology]

[0002] An all-solid-state battery is a battery having a solid electrolyte layer between a positive electrode active material layer and a negative electrode active material layer, and has an advantage that it is easier to simplify safety devices compared to liquid batteries having an electrolyte solution containing a flammable organic solvent. A sulfide solid electrolyte is known as a solid electrolyte used in all-solid-state batteries.

[0003] For example, Patent Document 1 discloses a method for producing an ion conductor (sulfide solid electrolyte), which includes mixing LiBH4 and P2S5 in a molar ratio of LiBH4:P2S5=x:(1-x) [wherein x=more than 0.85 and 0.98 or less] to obtain a mixture, and heat-treating the mixture, as well as the ion conductor (sulfide solid electrolyte) produced by the method.

[0004] In addition, Non-Patent Document 1 discloses a sulfide solid electrolyte represented by (100-x)(0.75Li2S·0.25P2S5)·xLiBH4. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2016 / 103894 [Non-patent literature]

[0006] [Non-Patent Document 1] Mechanochemically Prepared Li2S P2S5 LiBH4 Solid Electrolytes with an Argyrodite Structure(ACS Omega 2018, 3, 5453 5458)

Summary of the Invention

Problems to be Solved by the Invention

[0007] From the perspective of improving battery performance, a solid electrolyte with good ionic conductivity is required. The present disclosure has been made in view of the above circumstances, and the main object thereof is to provide a sulfide solid electrolyte with good ionic conductivity.

[0008] The present disclosure has been made in view of the above circumstances, and the main object thereof is to provide a sulfide solid electrolyte with good ionic conductivity.

Means for Solving the Problems

[0009] [1] A sulfide solid electrolyte used in an all-solid-state battery, having a composition represented by (100 - x)[yLi2S·(1 - y)P2S5]·xLiBH4 (where x is a number satisfying 50 < x < 75, and y is a number satisfying 0.72 ≤ y ≤ 0.78), and having an ionic conductivity at 25°C of 5.0 mS / cm or more.

[0010] [2] The sulfide solid electrolyte according to [1], wherein the ionic conductivity is 8.0 mS / cm or more.

[0011] [3] The sulfide solid electrolyte according to [1] or [2], having one peak in the range of 2θ = 13° or more and 16° or less in X-ray diffraction measurement using CuKα rays.

[0012] [4] A method for producing a sulfide solid electrolyte according to any one of [1] to [3], comprising: a first mechanical milling step of mechanically milling a mixture containing Li2S and P2S5 to obtain a first sulfide glass; and a second mechanical milling step of adding LiBH4 to the first sulfide glass and mechanically milling the resulting mixture to obtain a second sulfide glass, wherein the first mechanical milling step and the second mechanical milling step are each performed such that gravity Gn1 calculated from the following mathematical formula (1) is 6 G or more.

number

[0013] [5] The method for producing a sulfide solid electrolyte according to [4], wherein Gn1 is 15G or more.

[0014] [6] The method for producing a sulfide solid electrolyte according to [4] or [5], further comprising a heat treatment step of heat-treating the sulfide glass, wherein the heat treatment is performed at a temperature of 190° C. or lower.

[0015] [7] An all-solid-state battery having a positive electrode active material layer, a negative electrode active material layer, and a solid electrolyte layer disposed between the positive electrode active material layer and the negative electrode active material layer, wherein at least one of the positive electrode active material layer, the negative electrode active material layer, and the solid electrolyte layer contains the sulfide solid electrolyte according to any one of [1] to [3]. Effect of the Invention

[0016] The present disclosure has an effect of providing a sulfide solid electrolyte having good ion conductivity. [Brief description of the drawings]

[0017] [Figure 1] It is a flowchart illustrating a method for manufacturing a sulfide solid electrolyte in the present disclosure. [Diagram 2] It is a schematic cross-sectional view illustrating a all-solid-state battery in the present disclosure. [Diagram 3] It is a graph showing the measurement results of ionic conductivity in the examples. [Figure 4] It is a graph showing the measurement results of X-ray diffraction in the examples. [Diagram 5] It is a graph showing the measurement results of discharge capacity retention rate in the examples. [Figure 6] It is a graph showing the measurement results of ionic conductivity in the examples.

Embodiments for Carrying Out the Invention

[0018] Hereinafter, the sulfide solid electrolyte, the method for manufacturing the sulfide solid electrolyte, and the all-solid-state battery in the present disclosure will be described in detail.

[0019] A. Sulfide solid electrolyte The sulfide solid electrolyte in the present disclosure is a sulfide solid electrolyte used in an all-solid-state battery, and has a composition represented by (100−x)[yLi2S·(1−y)P2S5]·xLiBH4 (where x is a number satisfying 50 < x < 75, and y is a number satisfying 0.72 ≦ y ≦ 0.78), and the ionic conductivity at 25° C. is 5.0 mS / cm or more.

[0020] In the present disclosure, since it exhibits an ionic conductivity of 5.0 mS / cm or more within a predetermined composition range, it becomes a sulfide solid electrolyte having good ionic conductivity.

[0021] Here, the sulfide solid electrolyte disclosed in Patent Document 1 does not use Li2S, and has a maximum ionic conductivity of 2.0 mS / cm (measured at 27°C). The sulfide solid electrolyte disclosed in Non-Patent Document 1 has a maximum ionic conductivity of 1.8 mS / cm (measured at 25°C). In contrast, the sulfide solid electrolyte in the present disclosure has an ionic conductivity of 5.0 mS / cm or more in a given composition, and has significantly better ionic conductivity than the sulfide solid electrolyte in the above-mentioned document.

[0022] The sulfide solid electrolyte in the present disclosure has a composition represented by (100-x)[yLi2S·(1-y)P2S5]·xLiBH4. In the above composition, x is a number greater than 50, and may be a number equal to or greater than 52, a number equal to or greater than 55, or a number equal to or greater than 60. On the other hand, x is a number smaller than 75, and may be a number equal to or less than 70, a number equal to or less than 67, a number equal to or less than 65, or a number equal to or less than 63. In addition, in the above composition, y may be a number equal to or greater than 0.72, and may be a number equal to or greater than 0.73. On the other hand, y may be a number equal to or less than 0.78, and may be a number equal to or less than 0.75. In particular, y is preferably a number that allows the Li3PS4 structure to be mainly obtained in the first mechanical milling step described later. In particular, it is preferable that y is 0.75, that is, the ratio of Li2S to P2S5 is 75:25.

[0023] The sulfide solid electrolyte of the present disclosure has an ionic conductivity of 5.0 mS / cm or more at 25° C. The ionic conductivity may be 5.3 mS / cm or more, 5.5 mS / cm or more, 6.0 mS / cm or more, 8.0 mS / cm or more, or 10.0 mS / cm or more.

[0024] The sulfide solid electrolyte in the present disclosure may be a sulfide glass, a crystallized sulfide glass (glass ceramics), or a crystalline material obtained by subjecting a mixture to a solid-phase reaction treatment.

[0025] The sulfide glass can be obtained by amorphous processing of a mixture containing Li2S, P2S5, and LiBH4. Examples of the amorphous processing include mechanical milling. Mechanical milling will be described later.

[0026] Crystallized sulfide glass can be obtained, for example, by heat treating sulfide glass at a temperature equal to or higher than the crystallization temperature.

[0027] In addition, the sulfide solid electrolyte of the present disclosure preferably has one peak in the range of 2θ=13° or more and 16° or less in X-ray diffraction measurement using CuKα radiation. "Having one peak in the range of 2θ=13° or more and 16° or less" means that one peak top is observed in the range of 2θ=13° or more and 16° or less. When a shoulder peak is observed, the shoulder peak itself is regarded as one peak.

[0028] The sulfide solid electrolyte of the present disclosure is used in an all-solid-state battery, which will be described later.

[0029] B. Method for producing sulfide solid electrolyte Fig. 1 is a flow diagram illustrating a method for producing a sulfide solid electrolyte according to the present disclosure. As shown in Fig. 1, the method for producing a sulfide solid electrolyte according to the present disclosure is the method for producing a sulfide solid electrolyte described above, and includes at least a first mechanical milling step and a second mechanical milling step.

[0030] 1. First mechanical milling process The first mechanical milling step in the present disclosure is a step of mechanically milling a mixture containing Li2S and P2S5 to obtain a first sulfide glass.

[0031] The ratio of Li2S and P2S5 in the mixture is not particularly limited as long as the above-mentioned sulfide solid electrolyte is obtained. In other words, the ratio (molar ratio) of Li2S and P2S5 is y:1-y (0.72≦y≦0.78) in the above-mentioned composition formula.

[0032] In the first mechanical milling step, mechanical milling is performed so that the gravity Gn1 calculated from the following formula (1) is 6 G or more. The following formula (1) is a formula for converting the force applied in mechanical milling into gravity. Note that Gn1 can also be regarded as gravitational acceleration. By performing mechanical milling so that the gravity conversion is 6 G or more, a first sulfide glass in which a Li3PS4 skeleton is well formed can be obtained. By using such a first sulfide glass, a sulfide solid electrolyte with good ionic conductivity can be obtained.

[0033]

number

[0034] Gn1 calculated from the formula (1) may be 8 G or more, 10 G or more, 15 G or more, or 18 G or more. On the other hand, Gn1 may be, for example, 25 G or less, 22 G or less, or 20 G or less.

[0035] The time for mechanical milling in the first mechanical milling step is not particularly limited, and is, for example, 5 hours or more and 24 hours or less.

[0036] The type of mechanical milling may be wet mechanical milling or dry mechanical milling, and examples of the mechanical milling include ball mills such as planetary ball mills.

[0037] 2. Second mechanical milling process The second mechanical milling step in the present disclosure is a step of adding LiBH4 to the first sulfide glass and subjecting the glass to mechanical milling to obtain a second sulfide glass.

[0038] The ratio of the first sulfide glass to LiBH4 is not particularly limited as long as the above-mentioned sulfide solid electrolyte can be obtained. In other words, the ratio (molar ratio) of the first sulfide glass to LiBH4 is 100-x:x (50 <x<75)である。

[0039] In the second mechanical milling step, mechanical milling is performed so that the gravity Gn1 calculated from the above formula (1) is 6 G or more. Formula (1) and Gn1 are the same as above. In the first mechanical milling step and the second mechanical milling step, Gn1 may be the same or different.

[0040] The time and type of mechanical milling in the second mechanical milling step are similar to those in the first mechanical milling step described above.

[0041] 3.Heat treatment process The method for producing a sulfide solid electrolyte according to the present disclosure may include a heat treatment step of heat treating the sulfide glass, the heat treatment being performed at a temperature of 190° C. or lower.

[0042] It is presumed that if the heat treatment temperature is too high, a different phase may be formed in the obtained sulfide solid electrolyte. On the other hand, it is presumed that by setting the heat treatment temperature to 190°C or less, the formation of different phases is suppressed, and a sulfide solid electrolyte with better ionic conductivity (a sulfide solid electrolyte with good crystallinity) is obtained. This is presumed to be because the hydride (LiBH4) used in the sulfide solid electrolyte of the present disclosure undergoes a phase transition at around 400K (127°C) and exhibits good ionic conductivity in the hexagonal structure, which is a high-temperature phase.

[0043] The temperature of the heat treatment is, for example, 50° C. or more, and may be 75° C. or more, or 100° C. or more. On the other hand, the temperature of the heat treatment is 190° C. or less, and may be 160° C. or less, or 150° C. or less.

[0044] The heat treatment time is not particularly limited and can be appropriately adjusted depending on the heat treatment temperature, and is, for example, 30 minutes or more and 4 hours or less.

[0045] 4.Sulfide solid electrolyte The sulfide solid electrolyte produced by the above-mentioned method is similar to that described in "A. Sulfide solid electrolyte", and therefore will not be described here.

[0046] C. All-solid-state battery The sulfide solid electrolyte of the present disclosure is used in an all-solid-state battery. That is, the present disclosure can also provide an all-solid-state battery having a positive electrode active material layer, a negative electrode active material layer, and a solid electrolyte layer disposed between the positive electrode active material layer and the negative electrode active material layer, in which at least one of the positive electrode active material layer, the negative electrode active material layer, and the solid electrolyte layer contains the sulfide solid electrolyte.

[0047] In the all-solid-state battery according to the present disclosure, at least one of the positive electrode active material layer, the negative electrode active material layer, and the solid electrolyte layer contains the above-mentioned sulfide solid electrolyte, and therefore the all-solid-state battery has a good discharge capacity retention rate.

[0048] Fig. 2 is a schematic cross-sectional view illustrating an all-solid-state battery according to the present disclosure. The all-solid-state battery 10 shown in Fig. 2 has a positive electrode active material layer 1, a negative electrode active material layer 2, and a solid electrolyte layer 3 disposed between the positive electrode active material layer 1 and the negative electrode active material layer 2. The all-solid-state battery 10 also has a positive electrode current collector 4 that collects electrons from the positive electrode active material layer 1, and a negative electrode current collector 5 that collects electrons from the negative electrode active material layer 2. At least one of the positive electrode active material layer 1, the negative electrode active material layer 2, and the solid electrolyte layer 3 contains the sulfide solid electrolyte described above.

[0049] 1.Cathode active material layer The positive electrode active material layer contains at least a positive electrode active material. The positive electrode active material layer preferably contains at least one of a solid electrolyte, a conductive material, and a binder, as necessary. The positive electrode active material, the conductive material, and the binder may be any of conventionally known materials. In addition, the positive electrode active material layer preferably contains the above-mentioned sulfide solid electrolyte as a solid electrolyte.

[0050] 2.Negative electrode active material layer The negative electrode active material layer contains at least a negative electrode active material. The negative electrode active material layer preferably contains at least one of a solid electrolyte, a conductive material, and a binder, as necessary. The negative electrode active material, the conductive material, and the binder may be any of conventionally known materials. In addition, the negative electrode active material layer preferably contains the above-mentioned sulfide solid electrolyte as a solid electrolyte.

[0051] 3.Solid active material layer The solid electrolyte layer contains at least a solid electrolyte, and may contain a binder as necessary. The binder is as described above. The solid electrolyte is preferably the sulfide solid electrolyte described above.

[0052] 4. Positive and negative electrode current collectors The material of the positive electrode current collector and the negative electrode current collector can be a conventionally known metal material, such as Al, SUS, Cu, or Ni.

[0053] 5.All-solid-state battery The all-solid-state battery in the present disclosure is typically a lithium-ion secondary battery. In addition, the use of the all-solid-state battery includes, for example, a power source for vehicles such as a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV), an electric vehicle (BEV), a gasoline vehicle, and a diesel vehicle. In particular, it is preferable to use the all-solid-state battery as a driving power source for a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV), or an electric vehicle (BEV). In addition, the all-solid-state battery may be used as a power source for a moving body other than a vehicle (for example, a train, a ship, or an aircraft), or may be used as a power source for an electric product such as an information processing device.

[0054] The present disclosure is not limited to the above-described embodiment. The above-described embodiment is merely an example, and any configuration that is substantially the same as the technical idea described in the claims of the present disclosure and that exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES

[0055] [Example 1-1] Li2S (Mitsuwa Chemical) and P2S5 (Merck) were prepared as raw materials in a molar ratio of 75:25. These were dry-milled (ball diameter 5 mm, container 80 mL, rotation speed 510 rpm, operation time 10 hours) to obtain the first sulfide glass (0.75Li2S 0.25P2S5) (first mechanical milling step). LiBH4 (Aldrich) was added to the first sulfide glass so that the molar ratio of the first sulfide glass and LiBH4 was 48:52, and this was dry-milled (ball diameter 5 mm, container 80 mL, rotation speed 510 rpm, operation time 15 hours) (second mechanical milling step). As a result, a sulfide solid electrolyte (second sulfide glass) with a composition of 48(0.75Li2S 0.25P2S5) 52LiBH4 was obtained. The above composition corresponds to the composition of (100-x)[yLi2S·(1-y)P2S5]·xLiBH4 where x = 52 and y = 0.75. The mechanical milling equipment used was a Fritsch Planetary Ball Mill Premium Line PL-7.

[0056] Here, in the mechanical milling device, the revolution radius rs was 0.07 m, the container radius rp1 was 0.0240 m, and the ratio of rotation to revolution iw was -2.0. The gravity Gn1 calculated by substituting these values ​​and the above rotation speed into the above formula (1) was 18 G for both the first mechanical milling process and the second mechanical milling process.

[0057] [Examples 1-2 to 1-5 and Comparative Examples 1-1 to 1-7] A sulfide solid electrolyte was prepared in the same manner as in Example 1-1, except that the ratios of Li2S, P2S5, and LiBH4 were changed so that the composition of the sulfide solid electrolyte would be the values shown in Table 1 below.

[0058] [Evaluation 1] (Measurement of ionic conductivity) Each of the sulfide solid electrolytes of Examples 1-1 to 1-5 and Comparative Examples 1-1 to 1-7 was weighed in the range of 0.08 g to 0.1 g, pressed at a pressure of 6 t, and pelletized. Then, impedance measurement was performed at 25°C. Using the obtained resistance value R (Ω), the thickness L (cm) of the pellet, and the bottom area A (cm 2 ), the ionic conductivity (σ) was calculated from the following formula. The results are shown in Figure 3 and Table 1. σ = L / (RA)

[0059]

Table 1

[0060] As shown in Figure 3 and Table 1, it was confirmed that there is a peak in the ionic conductivity in the range of 50 < x < 75, and a good ionic conductivity (5.0 mS / cm or more) is exhibited.

[0061] (X-ray diffraction measurement) Each of the sulfide solid electrolytes of Examples 1-1 to 1-5 and Comparative Examples 1-1 to 1-7 was subjected to X-ray diffraction measurement under the conditions of room temperature in an Ar atmosphere. As the apparatus, a Rigaku full-automatic multi-purpose X-ray diffractometer SmartLab was used, and the X-ray was CuKα ray (λ = 1.5404 Å). The results are shown in Figures 4(a) and (b). Note that Figure 4(b) is an enlarged view of Example 1-3 (x = 58) and Comparative Example 1-7 (x = 83) in Figure 4(a).

[0062] As shown in Fig. 4(a), when x was too low, no peak was observed in the range of 2θ = 13° or more and 16° or less. Also, as shown in Fig. 4(b), in Example 1-3, one peak was observed in the range of 2θ = 13° or more and 16° or less, but in Comparative Example 1-7, two peaks including a shoulder were observed. Although not shown, two peaks were also observed in other Comparative Examples, similar to Comparative Example 1-7.

[0063] (Measurement of Discharge Capacity Retention Rate) Using the sulfide solid electrolytes of Examples 1-3 and Comparative Examples 1-4, batteries for evaluation were fabricated as follows. First, the sulfide solid electrolyte was finely granulated by mechanical milling in a mixed solvent of heptane and dibutyl ether. Then, it was dried at 100°C for 2 hours. Then, it was mixed with spherical graphite in a volume ratio of 35:65 to fabricate a negative electrode composite. The negative electrode composite, separator layer, and counter electrode (Li-In foil) were laminated in this order. In this way, a battery for evaluation (negative electrode half cell) was fabricated. For the separator layer, the sulfide solid electrolyte (second sulfide glass) after the second mechanical milling process was used.

[0064] Each of the obtained evaluation batteries was subjected to three cycles of CCCV charging and discharging at 0.1 C at 25 °C. In the CCCV charging and discharging, the cut-off voltage was 0.05 V (Li + / Li) and the cutoff current was 0.01C. Then, the charge rate was changed from 0.1 to 0.5C, and the discharge rate was fixed at 0.1C, and CC charge / discharge was performed. The cutoff voltage in CC charge / discharge was 0.05V (Li + The capacity during CC charging and discharging was divided by the initial capacity to calculate the discharge capacity retention rate (%). The results are shown in Figure 5.

[0065] 5, the higher the charge rate, the larger the charge / discharge capacity in Example 1-3 was compared to Comparative Example 1-4. In particular, when the charge rate was 0.5 C, Example 1-3 had a capacity retention rate 1.2 times higher than Comparative Example 1-4.

[0066] [Example 2-1] A sulfide solid electrolyte was prepared in the same manner as in Example 1-1, except that the ratios of Li2S, P2S5, and LiBH4 were changed so that the composition of the sulfide solid electrolyte was 46(0.75Li2S 0.25P2S5) 54LiBH4. The above composition corresponds to the composition of (100-x)[yLi2S (1-y)P2S5] xLiBH4 where x = 54 and y = 0.75.

[0067] [Comparative Example 2-1] A sulfide solid electrolyte was produced in the same manner as in Example 2-1, except that in the first mechanical milling step, the ball diameter was set to 4 mm, the rotation speed was set to 280 rpm, so that the gravity Gn1 calculated from the formula (1) was changed to 5.4 G, and the operation time was changed to 45 hours.

[0068] [Rating 2] (Measurement of ionic conductivity) For the sulfide solid electrolytes of Example 2-1 and Comparative Example 2-1, the ionic conductivity was measured in the same manner as in Evaluation 1. The results are shown in Table 2.

[0069] [Table 2]

[0070] As shown in Table 2, it was confirmed that the ion conductivity was improved by performing mechanical milling so that Gn1 was 6 G or more in the first mechanical milling step and the second mechanical milling step. This is presumably because the Li3PS4 framework was better formed.

[0071] [Example 3-1] A sulfide solid electrolyte (sulfide glass) having a composition of 42(0.75Li2S 0.25P2S5) 58LiBH4 was obtained in the same manner as in Example 1-3. The obtained sulfide glass was heated at a temperature of 60°C for 2 hours. The sulfide solid electrolyte after heating was used as an evaluation sample.

[0072] [Examples 3-2 to 3-4] Except for changing the heat treatment temperature as shown in Table 3, the same procedure as in Example 3-1 was carried out to obtain a sulfide solid electrolyte (evaluation sample).

[0073] [Rating 3] (Measurement of ionic conductivity) The ionic conductivity of the sulfide solid electrolytes of Examples 3-1 to 3-4 was measured in the same manner as in Evaluation 1. The results are shown in Table 3 and Fig. 6 together with the results of Example 1-3. Note that, although it can be considered that no heat treatment was performed in Example 1-3, for the sake of convenience, the heat treatment temperature is described as room temperature (25°C).

[0074] [Table 3]

[0075] As shown in FIG. 6 and Table 3, it was confirmed that good ionic conductivity was obtained by heat treatment at 190° C. or less, and that ionic conductivity was further improved by heat treatment at 160° C. or less. In addition, the ionic conductivity was highest when heat treatment was performed at 100° C. The hydride (LiBH4) used in the sulfide solid electrolyte in the present disclosure undergoes a phase transition near 400 K (127° C.). It is known that LiBH4 improves its ionic conductivity by changing from an orthorhombic structure, which is a low-temperature phase, to a hexagonal structure, which is a high-temperature phase. Therefore, it is presumed that the ionic conductivity of the sulfide solid electrolyte using LiBH4 was highest when heat treatment was performed at 100° C., which is near the phase transition temperature. It is also presumed that the sulfide solid electrolyte using LiBH4 was well converted into glass ceramics by heat treatment at around 100° C., and the ionic conductivity was improved. [Explanation of symbols]

[0076] 1...Cathode active material layer 2...Negative electrode active material layer 3...Solid electrolyte layer 4...Positive electrode current collector 5...Negative electrode current collector 10...All-solid-state battery

Claims

1. A sulfide solid electrolyte for use in an all-solid-state battery, (100-x)[yLi 2 S (1-y) P 2 S 5 ]・xLiBH 4 (wherein x is a number satisfying 50<x<75, and y is a number satisfying 0.72≦y≦0.78), A sulfide solid electrolyte having an ionic conductivity of 5.0 mS / cm or more at 25° C.

2. The sulfide solid electrolyte according to claim 1, wherein the ionic conductivity is 8.0 mS / cm or more.

3. In the X-ray diffraction measurement using CuKα radiation, The sulfide solid electrolyte according to claim 1, having one peak in the range of 2θ = 13° or more and 16° or less.

4. A method for producing a sulfide solid electrolyte according to any one of claims 1 to 3, Li 2 S and P 2 S 5 A first mechanical milling step of mechanically milling a mixture containing the above to obtain a first sulfide glass; The first sulfide glass is added with LiBH 4 and a second mechanical milling step of adding and mechanically milling to obtain a second sulfide glass, A method for producing a sulfide solid electrolyte, wherein in the first mechanical milling step and the second mechanical milling step, each of the mechanical milling steps is performed so that a gravity Gn1 calculated from the following formula (1) is 6 G or more. [0010] (In formula (1), rs is the revolution radius, rp1 is the radius of the container used in mechanical milling, iw is the ratio of rotation to revolution, π is the circular constant, and rpm is the revolution speed.)

5. The method for producing a sulfide solid electrolyte according to claim 4, wherein the Gn1 is 15G or more.

6. The method includes a heat treatment step of heat treating the sulfide glass, The method for producing a sulfide solid electrolyte according to claim 4, wherein the temperature in the heat treatment is 190°C or lower.

7. An all-solid-state battery having a positive electrode active material layer, a negative electrode active material layer, and a solid electrolyte layer disposed between the positive electrode active material layer and the negative electrode active material layer, An all-solid-state battery, wherein at least one of the positive electrode active material layer, the negative electrode active material layer, and the solid electrolyte layer contains the sulfide solid electrolyte according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Solid electrolyte material and solid-state battery manufactured using the same

    JP2023518850A

  • Ion conductor and method for producing same

    WO2016103894A1